Exceptional ultraviolet photovoltaic response of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline based detector - Cai, Yuhua; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Zhao, Jun; Yuan, Jun; Duan, Yu; Hu, Yanbo; Tai, Yunjian; Zhao, Jianhong (Journal of applied physics, 2015)
UV photodetector is a kind of important optoelectronic devices that has vital applications in both scientific and engineering fields. The development of UV photodetectors has been impeded because of lacking stable p-type wide-gap semiconductor which is crucial for high-performance, low-cost, large-array UV photovoltaic detector. In this paper, we report a novel UV photovoltaic detector fabricated using 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) as a sole photoactive material. The highest detectivity (D*) reaches 9.02 × 1011 cm Hz1/2 W−1 at −1 V bias voltage at room temperature under 365 nm illumination for the un-optimized BCP based detector (without using pre-amplifier), which is the highest value for the sole UV organic photoactive material based photovoltaic detector. The optical, electrical, and photovoltaic properties, including the UV absorption, photoluminescence (PL) emission, PL excitation, I-V, C-V, and photoresponse, have been systematically investigated to disclose the internal mechanism. The present study paves the way for developing high-performance, low-cost UV focal plane array detectors.